2016
DOI: 10.1111/pce.12688
|View full text |Cite
|
Sign up to set email alerts
|

Grapevine petioles are more sensitive to drought induced embolism than stems: evidence from in vivo MRI and microcomputed tomography observations of hydraulic vulnerability segmentation

Abstract: The 'hydraulic vulnerability segmentation' hypothesis predicts that expendable distal organs are more susceptible to water stress-induced embolism than the main stem of the plant. In the current work, we present the first in vivo visualization of this phenomenon. In two separate experiments, using magnetic resonance imaging or synchrotron-based microcomputed tomography, grapevines (Vitis vinifera) were dehydrated while simultaneously scanning the main stems and petioles for the occurrence of emboli at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
68
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 42 publications
6
68
1
1
Order By: Relevance
“…To facilitate the observation of leaf appearance at different stages, the same leaf is outlined in red in all three images. accordance with the hydraulic segmentation known in grapevine (Charrier et al, 2016;Hochberg et al, 2016a), the stems of dehydrated grapevine showed only 7% PLC, close to the average value of control plants (Fig. 7).…”
Section: Experiments 1: Dehydration By Cutting the Root-stem Junctionsupporting
confidence: 88%
See 1 more Smart Citation
“…To facilitate the observation of leaf appearance at different stages, the same leaf is outlined in red in all three images. accordance with the hydraulic segmentation known in grapevine (Charrier et al, 2016;Hochberg et al, 2016a), the stems of dehydrated grapevine showed only 7% PLC, close to the average value of control plants (Fig. 7).…”
Section: Experiments 1: Dehydration By Cutting the Root-stem Junctionsupporting
confidence: 88%
“…Visualization techniques such as microcomputed tomography (microCT) and magnetic resonance imaging (MRI) provide reliable measurements of xylem embolism in intact plants (Scheenen et al, 2007;Cochard et al, 2015) and even embolism propagation over time in the same plant (Holbrook et al, 2001;Brodersen et al, 2010Brodersen et al, , 2013Choat et al, 2015;Hochberg et al, 2016a). However, these approaches also have drawbacks: small field of view, long acquisition times, potentially lethal radiation doses for the imaged plant (in the case of microCT), expense, and limited availability of the equipment.…”
mentioning
confidence: 99%
“…Thus, changes in outside-xylem pathways with dehydration could be more reversible during drought and recovery cycles than xylem embolism. While xylem embolism requires several hours under no tension to recover by capillarity (Hochberg et al, 2016;Knipfer et al, 2016), in some species, K leaf can partially recover after only 1 h of rehydration , which could be due to the recovery of K ox . Future work should resolve the influence of K x and K ox decline on stomatal conductance and their recovery.…”
Section: Resultsmentioning
confidence: 99%
“…The gas molecules tend to accumulate together causing a disruption of the water column in the xylem and a decrease in hydraulic conductivity. Embolisms occur more frequently in roots and petioles than in shoots, causing 80%PLC (Percent Loss of hydraulic Conductivity) during a moderate water stress in these anatomical compartments compared to the 50% PLC of shoots (Lovisolo et al 2008a;Hochberg et al 2016). Root embolization is thought to limit water use by the plant and be protective against the propagation of low xylem tension to the stem.…”
Section: Root Response To Drought: Embolism Formation and Recoverymentioning
confidence: 99%